Analysis of the behavior of LED based street lighting over its useful - Costalonga, Álvaro Gotelip Tostes; Pereira, Elian Henrique Silva; Casagrande, Cristiano Gomes; Pinto, Danilo Pereira (ANAP Brazil, 2025)
Objective – This study aims to analyze the behavior of LED-based street lighting over its useful life, considering its efficiency, reliability, and performance over time. The research focuses on evaluating the average illuminance and luminance curves, identifying the impact of aging on the quality of urban lighting.Methodology – The study was conducted through the analysis of illuminance and luminance measurements throughout the lifespan of LED luminaires installed in a public lighting system. Data were collected over different operational periods, allowing a comparative assessment between the early years of operation and the end of the manufacturer-specified lifespan.Originality/relevance – This study fills a theoretical gap by empirically investigating the degradation of luminous efficiency in LED-based public lighting systems. The quantitative analysis contributes to assessing the durability and reliability of this technology, reinforcing its importance for public policies and energy efficiency strategies.Results – The findings indicate a progressive reduction in illuminance and luminance over time, although the values remain within the parameters established by the NBR 5101 standard. The study demonstrated that the LED system maintains satisfactory performance even after 50,000 hours of operation, suggesting a lifespan longer than estimated by manufacturers.Theoretical/methodological contributions – The research provides a systematic approach to evaluating the performance of LED-based public lighting systems, using real measurements and normative comparisons. Additionally, it highlights the importance of continuous monitoring of luminous degradation to optimize the maintenance and replacement of luminaires.Social and environmental contributions – The implementation of LED technology in public lighting promotes greater energy efficiency, reducing electricity consumption and maintenance costs. The study reinforces the importance of adopting sustainable urban lighting solutions, contributing to safer, more efficient, and environmentally responsible cities.
Keywords: Street Lighting; LED; Lighting technology; Illuminance